PENGARUH SENSE DALAM EXPERIENTIAL MARKETING TERHADAP BRAND EQUITY PEMANDIAN AIR PANAS CIWALINI-CIWIDEY KABUPATEN BANDUNG (Survei Pada Pengunjung Pemandian Air Panas Ciwalini-Ciwidey Kab. Bandung) - Novalita, Dewi Pancawati; Nurhayati, Lilis; Andari, Rini (THE Journal : Tourism and Hospitality Essentials Journal, 2011)
South Bandung is one of the districts in West Java province which offers nature tours and much in demand as a travel destination for people from various regions, especially during the weekend, one of which is the Hot Water Bathing Ciwalini-Ciwidey. Hot Water Bathing Ciwalini have contributed to the development of tourism Bandung regency, but in the year 2008 Bathing Water Heat Ciwalini traffic decreased by 2.2%. This is expected because of the level of brand equity Ciwalini Hot Water Bathing, because of declining traffic levels indicated in the brand equity Hot Water Bathing Ciwalini the less powerful. Therefore Ciwalini Hot Water Bathing should consider implementation of the sense in the experiential in order to improve brand equity Ciwalini Hot Water Bathing. In connection with these two research studies conducted on the influence of sense and feel of experiential marketing on brand equity Ciwalini Hot Water Baths. Problem studied is how the response to visitors on the implementation sense, how the responses regarding the implementation of visitor feel, how visitors respond to the brand equity Hot Water Bathing Ciwalini how the influence of a sense of brand equity Hot Water Bathing Ciwalini how the influence of a sense of brand equity Ciwalini Hot Water Bathing. As the population in this study are visitor Hot Water Bathing Ciwalini-Ciwidey Kab. Bandung. The sampling technique is a systematic random sampling. The method used was survey explanatory. The data used are primary data and secondary data. Analysis technique used is the regresion analysis. Hypothesis testing results indicate that the sense of the experiential marketing significant influence on brand equity Ciwalini Hot Water Baths.